Kyoto international consensus report on anatomy, pathophysiology and clinical significance of the gastro-oesophageal junction. Issue 8 (20th June 2022) - Sugano, Kentaro; Spechler, Stuart Jon; El-Omar, Emad M; McColl, Kenneth E L; Takubo, Kaiyo; Gotoda, Takuji; Fujishiro, Mitsuhiro; Iijima, Katsunori; Inoue, Haruhiro; Kawai, Takashi; Kinoshita, Yoshikazu; Miwa, Hiroto; et al.
Abstract : Objective: An international meeting was organised to develop consensus on (1) the landmarks to define the gastro-oesophageal junction (GOJ), (2) the occurrence and pathophysiological significance of the cardiac gland, (3) the definition of the gastro-oesophageal junctional zone (GOJZ) and (4) the causes of inflammation, metaplasia and neoplasia occurring in the GOJZ. Design: Clinical questions relevant to the afore-mentioned major issues were drafted for which expert panels formulated relevant statements and textural explanations. A Delphi method using an anonymous system was employed to develop the consensus, the level of which was predefined as ≥80% of agreement. Two rounds of voting and amendments were completed before the meeting at which clinical questions and consensus were finalised. Results: Twenty eight clinical questions and statements were finalised after extensive amendments. Critical consensus was achieved: (1) definition for the GOJ, (2) definition of the GOJZ spanning 1 cm proximal and distal to the GOJ as defined by the end of palisade vessels was accepted based on the anatomical distribution of cardiac type gland, (3) chemical and bacterial ( Helicobacter pylori ) factors as the primary causes of inflammation, metaplasia and neoplasia occurring in the GOJZ, (4) a new definition of Barrett's oesophagus (BO). Conclusions: This international consensus on the new definitions of BO, GOJ and the GOJZ will be instrumental in future studies aiming to resolve many issues on this important anatomic area and hopefully will lead to better classification and management of the diseases surrounding the GOJ.